Blood feud as gift exchange - Darovec, Darko (Acta Histriae, 2017)
The article, based on interdisciplinary historiographical and anthropological studies and archival documents, collected folk literature and other documents, will reconstruct the ritual of blood feud with emphasis on the act of humiliation and penance as refl ected in documents from Southeast Europe, comparing them with many fragments of medieval European cases, refl ecting general ritual structure in the fi eld of public aff airs: Homage (gift, first approach), Fides (fidelity, oath, truce) and Investiture (appointment), and, in case of dispute settlement, Pace Perpetua - lasting peace (love, marriage), with particular focus on principles of the so called gift-exchange societies. The hypothesis of this article, based on collected material and on outlined cases, is arguing in favour of the principle of the general ritual structure for all public aff airs, in which precisely the gesture of penance and humiliation plays an important symbolic role, especially in the ritual of vindicta, that is in the customary system of conflict resolution.
Keywords: čustva; Early Modern Period; emotions; emozione; faida; fajda; humiliation; maščevanje; medio evo; Middle Ages; penance; penitenza; pokora; ponižanje; rito processuale; ritual; rituale; satisfaction; sistem reševanja sporov; sistema di soluzione dei conflitti; soddisfazione; sodni postopek; srednji vek; system of conflict resolution; trial rites; umiliazione; vendetta; zadoščevanje; zgodnji novi vek